The architecture of markets : an economic sociology of twenty-first-century capitalist societies - Fligstein, Neil (Princeton University Press, 2001)
"Addressing the unruly dynamism that capitalism brings with it, leading sociologist Neil Fligstein argues that the basic drift of any one market and its actors, even allowing for competition, is toward stabilization."